DESIGN & ANALYSIS OF STEERING SYSTEM DRAG LINK AGAINST BUCKLING LOADS FOR TIPPER APPLICATION - Yuvraj N. Doke; Prof. Sameer M. Shaikh (International Journal of Innovations in Engineering Research and Technology, 2021)
For tipper application, motion from steering wheel transferred to stub axle via steering column, steering gear box, pitman arm, drag link & steering arm to stub axle. Drag links are mainly subjected to compressive loads, which causes buckling failure of drag link tubes. This paper describes calculation of buckling strength for drag link. Also analysis of drag link tubes against compressive loads shown. Relations of various design parameters with buckling strength are shown, which will be useful for optimization of design parameters.